PERCERAIAN âSIRIâ (Studi Tentang Makna Perkawinan dan Tabu Pada Tujuh Kasus di Desa Sidodadi Kecamatan Padang Cermin, Kabupaten Pesawaran Lampung) - Syafriadi, Syafriadi; Sari, Yuni Ratna (SOCIOLOGIE, 2013)
Marriage is facility to form a family, marriage is also one of the important bit and sacral of life cycle a person, this is proven by arranging marriage ceremonies in our society, but although marriage held to be sacred but now meaning marriage is shifting, the divorce that happens in society, who including in divorce in family, that next researcher call âsirriâ divorce, so that problem in research is whether meaning marriage and meaning âsirriâ divorceÂ and taboo for village community Desa Sidodadi Kecamatan Padang Cermin Kabupaten Pesawaran,Lampung. The purpose of this research is review and analyze entendres theÂ meaning of marriage and the meaning ofâsirriâ divorceon seven cases in Desa Sidodadi Kecamatan Padang Cermin Kabupaten Pesawaran Lampung research method used is qualitative method with seveninformant. Data were collected by means of in-depth interviews and observations, and data analysis techniques used are the reduction of data, data presentation, and drawing conclusions. The results of this research show that the meaning of marriage to the informants belief that if they had found her soul mate then thats when they have to get married, while it is the meaning of divorce is a custom that prevails in the village and divorce is taboo.Keywords: Marriage, sirri, divorce